(untitled) - Roberts, J. M. (Oxford, 1996)
Oxford now presents the new, conveniently-sized and affordable A Short History of the World. Vividly written, it brings the outstanding breadth of scholarship and international scope of the larger History of the World within the grasp of every home, school, and library. Completely up to date and comprehensive yet succinct, it accompanies readers on an amazing journey from the first appearance of the species Homo sapiens up to the bloodshed in the former Yugoslavia and the latest chapter in the exploration of space. Surveying the major events, developments, and personalities that have shaped the civilazations of the world, from the arts, politics, and religion to scientific and technical breakthroughs, Roberts carefully ties in economic changes--such as trade routes and developments in agriculture and manufacturing--making clear their importance for the history of politics and changing societies. Throughout, he brilliantly tells the story of the growing power of humans to remake their world and control their own destiny. Effortlessly drawing together the great themes of civilization with details from everyday life, he brings readers face to face with the exciting, dramatic, often tragic story that is the history of the world.
Keywords: World history